2021
DOI: 10.1002/adfm.202102406
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Phenomena of Multi‐Way Sodium Storage in Selenide Electrode

Abstract: Transition-metal chalcogenides have gained special attention as potential anodes for Na-ion batteries due to their high capacities to originate from complex charge storage mechanisms. Although the sodium storage process in chalcogenides is still unclear, it is common to assume that it can occur via one of the following routes: intercalation, conversion, or alloying. In this paper, an anomalous multi-way mechanism in MoSe 2 electrode, including all three of the above scenarios, is reported. The intercyclic prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…3 Exemplary XAS spectra as measured with linearly polarized X-ray beam for both NiO (111) (left panel) and CoO(111) (right panel) antiferromagnetic films epitaxially grown on Fe(110)/W(110). The direction of the incoming X-rays is parallel to the sample normal and its linear polarization is parallel either to the Fe [1][2][3][4][5][6][7][8][9][10] or to Fe[001] in-plane direction including material science, surface physics, magnetism, and biological systems. The most successful projects were focused on charge storage materials related to Li-or Na-based batteries [6], superconductors [7], and magnetism of the multilayer systems [8][9][10][11][12][13].…”
Section: Present Status and Scientific Highlightsmentioning
confidence: 99%
“…3 Exemplary XAS spectra as measured with linearly polarized X-ray beam for both NiO (111) (left panel) and CoO(111) (right panel) antiferromagnetic films epitaxially grown on Fe(110)/W(110). The direction of the incoming X-rays is parallel to the sample normal and its linear polarization is parallel either to the Fe [1][2][3][4][5][6][7][8][9][10] or to Fe[001] in-plane direction including material science, surface physics, magnetism, and biological systems. The most successful projects were focused on charge storage materials related to Li-or Na-based batteries [6], superconductors [7], and magnetism of the multilayer systems [8][9][10][11][12][13].…”
Section: Present Status and Scientific Highlightsmentioning
confidence: 99%
“…[70] In a recent report, to avoid the interference of surface reactions on the ex situ characterization technique, Plewa et al used the in situ characterization method to further study the sodium storage mechanism of MoSe 2 electrode. [71] Through a series of in situ XRD, X-ray absorption near edge structure (XANES), XPS, and in situ electrochemical impedance spectroscopy (EIS) analyses, the authors innovatively reported an abnormal multistep sodium storage mechanism, namely an additional alloying reaction occurs simultaneously with the intercalation and conversion reactions during the first discharge and charge cycle, as depicted in Figure 4e.…”
Section: Initial Charge Productsmentioning
confidence: 99%
“…e) The sodium storage mechanisms of MoSe 2 . Reproduced with permission [71]. Copyright 2021, Wiley-VCH.…”
mentioning
confidence: 99%
“…High-efficiency electrical energy storage systems are important for modern society. Although lithium-ion batteries dominate the market for rechargeable high-energy batteries, its application in large-scale energy storage systems is still restricted due to the high manufacturing cost. Particularly, the use of highly toxic and combustible organic electrolytes may result in dangerous reactions between electrodes and electrolytes. Rechargeable aqueous metal-ion batteries, especially the recently developed zinc-ion batteries (ZIBs), are a candidate with great potential for large-scale energy storage systems, attributed to their ease of handing, environmental benignity, low potential, and safety. Similar to the traditional commercial alkaline zinc–manganese batteries, manganese-based oxides are regarded as ideal electrode materials for ZIBs because of their relatively high capacity and energy density, natural abundance, and low toxicity. , Therefore, many Mn-based electrodes have been successfully fabricated for ZIBs through different methods. For instance, Tan et al prepared a defective Mn 3 O 4 @C nanorod array electrode for ZIBs via carbonization from a Mn-metal–organic framework .…”
Section: Introductionmentioning
confidence: 99%